Learning to be Included - Duff, Cameron (Sense, 2013)
Inspiring consternation and praise in near equal measure, Deleuze (1995:143) once observed that “everything I’ve written is vitalistic, at least I hope it is, and amounts to a theory of signs and events”. This chapter proposes a pedagogy of signs and events, grounded in Deleuze’s vitalism and practised (or lived) according to the ethology that Deleuze derives from Spinoza. Such a pedagogy should, in turn, yield a novel ethics of the sign whereby the becomings that Deleuze (1994) regards as central to all life may be accelerated or promoted.